2003
DOI: 10.1002/prot.10314
|View full text |Cite
|
Sign up to set email alerts
|

Alpha helix shortening in 1522 MSP‐1 conserved peptide analogs is associated with immunogenicity and protection against P. falciparum malaria

Abstract: 1522 is a nonimmunogenic conserved high-activity binding peptide (HABP) belonging to Plasmodium falciparum MSP-1 protein N-terminal fragment. The key amino acids in binding to red blood cells (RBC) were identified and replaced by others having similar mass but different charge. Because conserved HABPs are not antigenic nor immunogenic, immunogenicity and protectivity studies were then conducted on them in the Aotus monkey. 1H-NMR studies included the lead peptide 1522 as well as the analogs 9782, 13446, 13448,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…In this sense, the role of the P. falciparum MSP-1 ligand in this parasite invasion of RBCs has been well documented, as well as some of its most relevant binding fragments, such as MSP-1 42-61 , MSP-1 202-221 , and MSP-1 1282-1301 (Cubillos et al, 2003;Espejo et al, 2002;Helg et al, 2003;Lioy et al, 2001). The MSP-1 43-53 peptide has also proven to be an immunodominant epitope when included in malaria vaccine formulations assessed in clinical trials (Graves et al, 1998;Patarroyo et al, 1987Patarroyo et al, , 1988.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this sense, the role of the P. falciparum MSP-1 ligand in this parasite invasion of RBCs has been well documented, as well as some of its most relevant binding fragments, such as MSP-1 42-61 , MSP-1 202-221 , and MSP-1 1282-1301 (Cubillos et al, 2003;Espejo et al, 2002;Helg et al, 2003;Lioy et al, 2001). The MSP-1 43-53 peptide has also proven to be an immunodominant epitope when included in malaria vaccine formulations assessed in clinical trials (Graves et al, 1998;Patarroyo et al, 1987Patarroyo et al, , 1988.…”
Section: Discussionmentioning
confidence: 98%
“…Field information and animal handling and housing were performed as previously reported (Cubillos et al, 2003).…”
Section: Msp-1 42-61 Pseudopeptides and In Vivo Testsmentioning
confidence: 99%
“…Numerous studies of Aotus monkeys being immunised with conserved HABPs have found that they were not immunogenic or protection-inducing since they did not induce the production of antibodies against the parasite or induce protection for these immunised monkeys against experimental challenge with a P. falciparum strain 100% infective for this specie (Bermúdez et al, 2005;Cifuentes et al, 2003a,b;Cubillos et al, 2003;Espejo et al, 2004Espejo et al, , 2001Purmova et al, 2002;Salazar et al, 2002;Torres et al, 2003).…”
Section: Elongation Of Native Conserved Habpsmentioning
confidence: 97%
“…Such modifications included displacing or shortening native molecule a-helix (Cifuentes et al, 2003b;Cubillos et al, 2003;Espejo et al, 2004;Espejo et al, 2001) or a-helicoid fragment appearing in those native HABPs having a random structure Bermú dez et al, 2005;Bermú dez et al, 2003) or b-turn III distortions (Cifuentes et al, 2003a;Purmova et al, 2002), thus stimulating a considerably improved immune response, increasing antibody titres and inducing protection in some Aotus monkeys against experimental challenge. Table 2 shows Aotus immunisation studies with their respective antibody titres against the parasite (determined by IFA) and their protection capacity regarding experimental challenge.…”
Section: Modified Habpsmentioning
confidence: 99%
See 1 more Smart Citation